Preparation method of high-thermal-conductivity radiation refrigeration composite film

By preparing the PVDF/ST composite film, the problem of poor effect in the cooling of internal heat source objects is solved, high thermal conductivity and wide spectrum band emission are achieved, and the cooling effect under sun irradiation is improved.

CN119144025APending Publication Date: 2024-12-17CHINA YANGTZE POWER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410984316.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing radiation refrigeration materials do not work well in cooling objects with internal heat sources and are difficult to effectively cool down, especially traditional materials can only cool objects slightly below or close to the ambient temperature.

Method used

Using the preparation method of PVDF/ST composite membrane, PVDF powder is added to the mixed solution of ST and DMF under a cell crusher, and heated in a water bath to completely dissolve it to form a PVDF/ST scraping solution, and then scraping. It is cured and dried on a metal aluminum substrate to form a composite film with high thermal conductivity and wide band emission capability.

Benefits of technology

Improve the thermal conductivity and radiation refrigeration performance of the composite film, so that it can effectively cool down under sun exposure, especially for objects with internal heat sources. Materials with high temperatures can more effectively emit heat into the air in the form of infrared rays, reducing the amount of The temperature of cooling the object.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144025A_ABST
    Figure CN119144025A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of films and radiation refrigeration, and particularly discloses a preparation method of a high-thermal-conductivity radiation refrigeration composite film, which comprises the following steps of: selecting polyvinylidene fluoride (PVDF) with high emission in an atmospheric window wave band as a polymer matrix material; strontium titanate (ST) powder with a high refractive index, a wide forbidden band coefficient and a high heat conductivity coefficient is selected as filling particles. The daytime radiation refrigeration performance of the composite film is optimized by adjusting the mass ratio of PVDF to ST and the thickness of the composite film, and the finally prepared composite film has the characteristics of high emissivity (2.5-25 microns) of middle and outer wave bands and high reflectivity of visible light-near infrared rays, also has the characteristics of flexibility, high heat conductivity and the like, and is suitable for large-scale production. Therefore, more cooling power can be provided for a cooled object (especially an object which is higher than the environment temperature and has an internal heat source).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thin films and passive refrigeration, and in particular relates to a method for preparing a high thermal conductivity radiation refrigeration composite film. Background Art

[0002] Solar radiation and the loss caused by equipment operation increase the surface and internal temperature of objects, especially in the summer when global temperatures are rising, which may affect the normal operation of equipment and even the safety of residents around it. Radiative cooling technology, which spontaneously dissipates heat into outer space through the atmospheric window (8-13 μm) without consuming any energy or releasing carbon dioxide, is promising because of its ease of use and scalability. At present, most researchers only create porous or filled dielectric particles to scatter sunlight on the basis of selective high-emission polymer materials to obtain high sunlight reflection ability to achieve radiative cooling performance. Few people design according to the needs of the application environment. Radiative cooling materials with only high sunlight reflectivity and high atmospheric window emissivity (selective emitters) do not have obvious cooling effects on cooling objects with internal heat sources. For objects with internal heat sources, their temperature is often higher than the ambient temperature. At this time, compared with selective emitter materials, broadband emission materials (with high emissivity in the entire mid-infrared band) can increase more cooling power, and high-temperature substances always transfer energy to low-temperature substances. Increasing the thermal conductivity of radiative cooling materials can provide more cooling power for the cooled objects. In real life, traditional radiative cooling methods can only be cooled to a temperature slightly lower than or close to the environment because the objects being cooled usually have a large heat capacity. Therefore, most of the time, the temperature of the cooled objects is higher than the ambient temperature. Therefore, how to prepare a radiative cooling material with high thermal conductivity has become a technical problem that technicians in this field need to solve urgently. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a high thermal conductivity radiation refrigeration composite film.

[0004] The technical solution adopted to solve the above technical problems is: a method for preparing a high thermal conductivity radiation refrigeration composite film, the preparation method includes two steps: preparation of a PVDF / ST composite film coating solution and molding of a PVDF / ST composite film. First, ST and DMF are mixed and dispersed under a cell crusher, and then PVDF powder is added to the evenly dispersed ST solution, and stirred and heated in a water bath to completely dissolve the PVDF powder in the ST solution. Finally, it is taken out and placed on a constant temperature heated magnetic stirrer to stir and obtain an evenly dispersed PVDF / ST coating solution. The second step is to prepare a PVDF / ST composite film, and the solution is scraped onto a clean AL substrate by scraping, and after being cured on a heated aluminum platform, it is placed in an oven to dry, and finally a PVDF / ST composite film is obtained.

[0005] The working parameters of the cell crusher are stirring for 3-5 s, stopping for 3-5 s, and a total time of 10-20 min.

[0006] The mass ratio of NN dimethylformamide to strontium titanate powder and PVDF powder is 10:1-3:1.

[0007] When adding PVDF powder to ST dispersion, it needs to be added while stirring to shorten its dissolution time and the residue of the drug on the volume wall; the working speed of the water bath is 300-500 r / min, the working temperature is 60-70 ℃, and the stirring time is 1.5-2.0h; the working speed of the magnetic stirrer is 800-1000 r / min, the working temperature is 60-70 ℃, and the stirring time is 4-5h.

[0008] The purpose of heating the aluminum table is to solidify the scraping liquid on the substrate and reduce the possibility of it falling off the substrate. The working temperature of the aluminum table is 90-100 ℃; the working temperature of the drying oven is 90-100 ℃, and the working time is 1-2 h.

[0009] The substrate is a metal aluminum plate polished with 240-grit sandpaper.

[0010] The beneficial effects of the present invention are as follows: the technical solution provided by the present application adopts two steps including the preparation of PVDF / ST composite film coating liquid and the molding of PVDF / ST composite film to prepare the radiant cooling composite film, wherein the molding of the PVDF / ST composite film is achieved by smearing the prepared PVDF / ST composite film coating liquid onto the substrate, then curing it on a heated aluminum table and moving it into a drying oven for drying. ST and PVDF form an interface that strongly scatters sunlight, so that the prepared PVDF / ST composite film has a high solar emissivity (R 0.5-0.8 μm=88%), thereby reducing the absorption of sunlight energy by the cooled object; at the same time, the filling of ST transforms PVDF from a selective emitter to a broadband emitter (E 2.5-25 μm =97%), which improves the ability of the cooled object to emit heat into the air in the form of infrared microwaves, so that the cooling composite film has the function of cooling under sunlight; the filling of ST in the composite film constructs a heat conduction channel, which improves the overall thermal conductivity of the composite film (the thermal conductivity coefficient is 1.97 W / (m·K)), thereby further improving the cooling ability of the composite film for objects with a temperature higher than the ambient temperature (or with an internal heat source). BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a scanning electron microscope image of the PVDF / ST composite membrane prepared in Example 1 of the present invention. Figure 2 Optical parameter diagrams of PVDF / ST composite films with different PVDF:ST mass ratios and different thicknesses prepared in Examples 1 and 2 of the present invention.

[0012] Figure 3 These are photos of the folding and curling of the PVDF / ST composite membrane prepared in Example 1 of the present invention.

[0013] Figure 4 This is a diagram showing the summer cooling effect of the PVDF / ST composite membrane with a substrate prepared in Example 2 of the present invention compared with commercial white paint.

[0014] Figure 5 This is a diagram showing the summer cooling effect of the PVDF / ST composite membrane with a substrate prepared in Example 2 of the present invention.

[0015] Figure 6 This is a diagram showing the summer cooling effect of the PVDF / ST composite membrane with and without a substrate and the PVDF film prepared in Example 2 of the present invention.

[0016] Figure 7 The temperature drop performance of the PVDF / ST composite film prepared in Example 2 of the present invention in an outdoor electric vehicle charger application scenario.

[0017] Figure 8 This is a finite element analysis thermal conductivity simulation diagram of the PVDF / ST composite membrane and the PVDF film prepared in Example 2 of the present invention.

[0018] Fig. 9 This is a temperature diagram of heat dissipation of composite membranes with different PVDF:ST mass ratios prepared in Example 1 of the present invention on a heating ceramic sheet. DETAILED DESCRIPTION

[0019] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0020] Example 1 The present invention conducts experiments on PVDF / ST radiative cooling composite films doped with different ST contents, and the specific methods are as follows: (1) Take 10 g of N-N-dimethylformamide and 0 g (0.5 g, 1 g, 5 g, 75 g) of strontium titanate powder, place them in a container for mixing, and use a cell crusher to disperse them for 10 min to prepare a strontium titanate dispersion.

[0021] (2) Weigh 1 g of PVDF and add it to the ST solution under magnetic stirring. Then heat it in a water bath at 300 r / min and 60°C for 1.5 h to dissolve it.

[0022] (3) Finally, move it to a magnetic stirrer at 800 r / min and 60 °C and stir for 4 h to obtain a PVDF / ST composite membrane coating liquid.

[0023] (4) Adjust the coating film thickness and apply the coating liquid onto the aluminum substrate that has been polished by sandpaper.

[0024] (5) Heat the aluminum heating table to 90 °C and place the scraped sample on it to allow it to cure for about 15 min.

[0025] (6) Move the cured sample to a drying oven at 90 °C and dry for 2 h to form a PVDF / ST composite membrane.

[0026] Example 2 The present invention conducts an experiment on the thickness of a PVDF / ST radiative cooling composite film having a PVDF:ST mass ratio of 1:1.75, and the specific method is as follows: (1) Take 10 g of N-N-dimethylformamide and 1.75 g of strontium titanate powder, place them in a container for mixing, and disperse them using a cell crusher for 10 min to prepare a strontium titanate dispersion.

[0027] (2) Weigh 1 g of PVDF and add it to the ST solution under magnetic stirring. Then heat it in a water bath at 300 r / min and 60 °C for 1.5 h to dissolve it.

[0028] (3) Finally, move it to a magnetic stirrer at 800 r / min and 60 °C and stir for 4 h to obtain a PVDF / ST composite membrane coating liquid.

[0029] (4) The coating film thickness was adjusted to 500 μm, 1000 μm, 1500 μm, and 2000 μm, and the coating liquid was applied onto the aluminum substrate polished by sandpaper.

[0030] (5) Heat the aluminum heating table to 90 °C and place the scraped sample on it to allow it to cure for about 15 min.

[0031] (6) Move the cured sample to a drying oven at 90 °C and dry for 2 h to form a PVDF / ST composite membrane.

[0032] The PVDF / ST composite film formed in Example 2 has the functions of reflecting sunlight and radiating the heat of objects into the air in the form of infrared rays, and also has good thermal conductivity.

[0033] Example 3 Temperature comparison of ST-filled PVDF composite film and pure PVDF film, substrate, and substrate covered with white paint in outdoor cooling test: Radiant cooling performance test was conducted using 5 identical test chambers developed by ourselves. Photo of the test chamber Figure 4 As shown in a, the test was conducted under clear summer weather conditions. The test was conducted from 10:30 to 14:00 on July 22 to July 23, 2023, for a period of 2 days. The test results are as follows Figure 4 As shown in bd. Figure 4 d is the wind speed and humidity data on the test day. Figure 4 b describes the surface temperature and chamber temperature of all test samples, as well as the sub-ambient temperature. Figure 4 As shown in Figure c, on the first day of the temperature test, the average surface temperature and cavity temperature of the AL substrate were 73.2 °C and 62.7 °C, respectively, and the average surface temperatures of the PVDF / ST / AL and PVDF / AL coatings were 53 °C and 67.2 °C, respectively, which were 20.2 °C and 6 °C lower than the surface temperature of the AL substrate, respectively. The cavity temperature was 7.4 °C and -1.2 °C lower than the cavity temperature of the AL substrate, respectively. On the second day of the temperature test, when the weather was clear, the surface cooling temperatures of the PVDF / ST / AL and PVDF / AL coatings relative to the substrate were 17.7 °C and 4.6 °C, respectively, and the cavity cooling temperatures were 5.92 °C and -1.84 °C, respectively. The cooling effect on the first day was better than that on the second day, which may be due to clouds or rheology. H in the atmosphere 2 O、CO 2The content of other ingredients at different times and the wind speed are also different, which may have a great impact on refrigeration. A careful observation will reveal that the surface or cavity temperature of all test samples is much higher than the actual ambient temperature, which may be caused by the greenhouse effect, but the specifications of all test equipment are the same, so the environment of all samples is almost the same, so the test results are true and valid. In addition, the product was compared with samples painted with commercial white paint. Test results are as follows Figure 4 As shown in the figure. The sample we prepared is 4.7 ℃ lower than the surface temperature and 3 ℃ lower than the cavity temperature. It can be seen that the PVDF / ST / AL sample has a better cooling effect among all the tested samples.

[0034] Example 4 Temperature comparison of PVDF / ST composite film with or without substrate and pure PVDF film in outdoor cooling test: Considering the application environment (protective box of electrical equipment), we chose metal AL as the substrate, but it will have heat accumulation phenomenon under the sun. Figure 6 As shown in a, we conducted outdoor cooling tests on samples with and without substrate to explore the effect of the metal substrate on the refrigeration performance of our prepared samples. Figure 6 b shows the surface temperature and cavity temperature of all samples. Figure 6 c is the air humidity and wind speed on the day of the test. It can be seen that PVDF / ST not only has good cooling performance, but also has good shielding ability, which may be related to the high refractive index of ST49. However, the AL substrate has a greater impact on the surface temperature of PVDF, and heat accumulation occurs on the substrate, reducing the cooling effect of its film. The sunlight that is not reflected and absorbed by PVDF is absorbed by the air in the cavity and converted into heat. Due to the shielding effect of PVDF, the inevitable heat exchange with the outside world is reduced, and the temperature in the PVDF cavity is higher than the sub-ambient temperature. The test results show that the AL substrate has little effect on surface cooling, but it has a certain promoting effect on cavity cooling.

[0035] Example 5 Temperature reduction performance of PVDF / ST composite film in outdoor electric vehicle charger application scenario: The preparation method of ST-doped PVDF radiative cooling composite film is as described in Example 2. In order to further confirm the cooling performance of our PVDF / ST composite film, we used infrared images to record the temperature of the PVDF / ST film covered part and the exposed part of the electric vehicle charger surface, such as Figure 7 As shown in a. A 5×5 cm PVDF / ST film is used to cover part of the charger surface. Figure 7As shown in a. The initial temperature is about 20 °C, and the temperature difference between the covered and uncovered surfaces is only 0.5 °C. After exposing the charger to sunlight for 1 minute, the temperature difference between the two sides reaches 4.7 °C, and after 15 minutes, the temperature difference between the two sides reaches 13.4 °C. It can be seen that the composite film we prepared has a good cooling effect. Afterwards, the PVDF / ST film was taken out of the charger, and the temperature infrared images of the five stages before sampling, 1 s after sampling, 5s after sampling, 10s after sampling, and 15s after sampling were recorded, as shown in Fig. Figure 7 As shown in Figure b, the cooling effect of the sample is more directly demonstrated. When the sample is taken out, we can see that the area covered by the PVDF / ST film is still a "green area"; 15 s after the sample is removed, the temperature of the PVDF / ST corresponding area is still 5.3°C lower than that of the uncovered area, which also proves the excellent cooling performance of PVDF / ST.

[0036] Example 6 Comparison of heat dissipation capacity between PVDF / ST composite membrane and pure PVDF film: The thermal conductivity of pure PVDF and PVDF / ST composite materials was measured by laser flash method, as shown in Table 1. It can be seen that the thermal conductivity of PVDF / ST composite material is about 10 times higher than that of pure PVDF. The reason for the high thermal conductivity of the composite material may be that the filling of ST particles reduces the interfacial thermal resistance of PVDF and the disordered state between the molecular chains, which promotes the heat transfer of phonons. In order to verify the good heat transfer performance of PVDF / ST composite membrane, a finite element simulation (FEM) model was established in the simulation software COMSOL, and the heat transfer behavior of PVDF / ST and PVDF composite membranes was simulated. First, in the membrane model, a boundary heat source is defined on one edge, and the heat flow is transferred from one part to another, and the heat transfer time is set to 1 s. At the same time, the temperature of PVDF / ST composite membrane and pure PVDF membrane along the specified direction is calculated, as shown in Figure 8 The results show that: in the whole heat exchange cycle, the heat transfer rate of PVDF / ST composite membrane is faster than that of pure PVDF, and after 1 s of heat exchange, the temperature distribution of PVDF / ST composite membrane is wider; in addition, Figure 8 b It can be seen that compared with the pure PVDF membrane, the temperature of the PVDF / ST composite membrane at 2.5 cm away from the heat source is higher, which proves that the PVDF / ST composite membrane has efficient heat transfer ability. This may be due to the interaction between the highly thermally conductive ST particles, which reduces the interfacial thermal resistance, reduces the disordered state between the PVDF molecular chains, and promotes the heat transfer of phonons, thereby improving the thermal conductivity.

[0037] In addition, we also used infrared thermal imaging technology to monitor the temperature changes of PVDF / ST composites and further explored the thermal conductivity of composite films with different ST contents. We placed a ceramic heating plate with a side length of 10 mm on the PVDF composites with different ST contents and connected a power supply with a constant voltage of 3 V (such as Fig. 9 a). Fig. 9 c and Fig. 9 d is the infrared thermal image and temperature of the ceramic heating plate after heating different materials for 160 s. Obviously, the temperature of the ceramic heating plate of the PS-1.75 composite material is lower than that of the ceramic heating plate of other composite samples. This is because the temperature diffusion zone of the PS-1.75 composite material is wider. The temperature changes of the center point P1 (also the center point of the ceramic heating plate) of different samples are shown in Figure 2. Fig. 9 c. After heating for 160 s, the P1 of the PS-1.75 composite material reaches an equilibrium value of ~60°C, which is much smaller than the surface of other composite materials. The results show that the heat dissipation performance of the PS-1.75 composite material is better than that of other PVDF composite materials. It can be seen that the composite material prepared by us has good heat dissipation.

[0038] Table 1 shows the thermal conductivity, thermal diffusion coefficient, specific heat capacity and relative density of the optimal PVDF / ST composite membrane prepared in Example 2 of the present invention and pure PVDF.

[0039] .

Claims

1. A method for preparing a high thermal conductivity radiation refrigeration composite film, characterized in that: The preparation method comprises two steps: preparation of PVDF / ST composite membrane coating liquid and molding of PVDF / ST composite membrane, wherein the molding of PVDF / ST composite membrane is achieved by coating the prepared PVDF / ST composite membrane coating liquid on a substrate and then curing and drying it.

2. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 1, characterized in that: First, NN dimethylformamide and strontium titanate powder are mixed at a certain mass ratio, and then dispersed by a cell crusher to obtain a strontium titanate dispersion.

3. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 2, characterized in that: The mass ratio of NN dimethylformamide to strontium titanate powder is 10:1-3, and the working parameters of the cell crusher are stirring for 3-5 s, stopping for 3-5 s, and a total time of 10-20 min.

4. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 2 or 3, characterized in that: After the ST dispersion is prepared, 1 part of PVDF powder is added thereto and completely dissolved in a water bath. The mixture is then moved to a magnetic stirrer for strong stirring to fully disperse the mixture, and finally a PVDF / ST composite membrane coating liquid is obtained.

5. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 4, characterized in that: When adding PVDF powder to ST dispersion, it needs to be added while stirring to shorten its dissolution time and the drug residue on the volume wall; the working speed of the water bath is 300-500 r / min, the working temperature is 60-70 ℃, and the stirring time is 1.5-2.0 h; the working speed of the magnetic stirrer is 800-1000 r / min, the working temperature is 60-70 ℃, and the stirring time is 4-5 h.

6. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 5, characterized in that: The prepared PVDF / ST composite membrane coating liquid was coated on a clean substrate by blade coating, and after being cured on a heated aluminum stage, it was placed in an oven to dry, thereby finally obtaining a PVDF / ST composite membrane.

7. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 6, characterized in that: The purpose of heating the aluminum table is to solidify the coating liquid on the substrate and reduce the possibility of it falling off the substrate. The working temperature of the aluminum table is 90-100℃; the working temperature of the drying oven is 90-100℃, and the working time is 1-2 hours.

8. The method for preparing a high thermal conductivity radiation refrigeration composite film according to claim 6, characterized in that: The substrate is a metal aluminum plate polished with 240-grit sandpaper.